Efecto de temperaturas y tiempos de escaldado sobre la textura del embutido vegetal funcional de frijoles rojos (phaseolus vulgaris l.) - Loor España, María Fernanda (2019)
The objective of the research was to evaluate the effect of the temperatures and scalding times on the texture of the functional vegetable sausage of red beans. The treatments consisted of three scalding temperatures (60, 70 and 80 ° C) for 10 and 20 minutes. The trial was conducted with a DCA and three replicates, the experimental unit consisted of 2.5 kg of sausage; To this product the textural properties that were measured through the Shimadzu texturometer were evaluated, at a temperature of 25 ° C, with a 500 N force cell, through penetration and compression tests. The firmness, chewiness and elasticity variables were highly significant both in simple effect of the factors and in the interaction, except for the interaction at day 1, 15 and 30 for the chewable variable; in all the variables the best statistical values were obtained in the treatments that received 80 ° C for 20 minutes; however, the treatment that presented a texture similar to common sausages was the one that received 70 ° C for 20 minutes. In the microbiological results, the treatments that received the highest temperature and scalding time had no presence of microorganisms as of day 15. Protein analysis using the Kjeldahl method resulted in a3b2 treatment with 4.59%. Regarding the sensory analysis, no significant differences were observed between the treatments. It is concluded that the best treatment is that a scalding temperature of 70 ° C was applied for 20 minutes.